Application of The Traditional Architecture Concept of Aceh in BSI Facade, Lhokseumawe City - Muhammad Ihsan; Armelia Dafrina; Hendra Aiyub (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2022)
Traditional architecture is an element of culture that grows and develops in tandem with the growth of a tribe and nation in an area. The BSI building in the city of Lhokseumawe is a public building whose main function is as a center for administrative and financial services for the community in the area. This building was previously known as the Mandiri bank in Lhokseumawe city and was acquired by Bank BSI due to regulations that applied to the Aceh region. The reason behind the appointment of the Lhokseumawe city BSI bank as a case study is because in physical appearance it can be identified that in its application of its form it adopts traditional Acehnese architecture, which generally commercial buildings such as banks have modern architectural forms. This study aims to determine the façade forming factors and the application of traditional Aceh architectural concepts to buildings and the adaptations that occur in buildings. This type of research is qualitative with data analysis using descriptive in its presentation. The method of data collection is carried out in stages, using observation and documentation. The results of this study indicate the influence of Acehnese traditional architecture or rumoh Aceh on the BSI building in Lhokseumawe city as a façade forming factor. Many elements are applied to the building as the application of local culture to the building.